Joint Transmit Power and Time-Switching Control for Device-to-Device Communications in SWIPT Cellular Networks - Lim, Dong-Woo; Kang, Joonhyuk; Chun, Chang-Jae; Kim, Hyung-Myung (IEEE communications letters, 2019)
In this letter, we consider the device-to-device (D2D) communication in cellular networks, where both the cellular user (CU) and the D2D receiver (DR) decode information and harvest the energy. Unlike the conventional D2D communications, we figure out that it is possible for the D2D pair to communicate without degrading the performance of the CU. Based on this observation, two schemes changing time duration of the D2D transmission are investigated for the D2D rate maximization subject to maintaining the CU performance. By analytically comparing the performance of the two schemes, we obtain useful insights into the D2D transmission in simultaneous wireless information and power transfer cellular networks. Furthermore, utilizing this analysis, a closed-form scheme is proposed for fading channels.